Efficacy of a recombinant Intimin, EspB and Shiga toxin 2B vaccine in calves experimentally challenged with Escherichia coli O157:H7 - Martorelli, Luisina (2018)
Escherichia coli O157:H7 is a zoonotic pathogen of global importance and the serotype of Shiga toxin-producing E. coli (STEC) most frequently associated with Hemolytic Uremic Syndrome (HUS) in humans. The main STEC reservoir is cattle. Vaccination of calves with the carboxy-terminal fraction of Intimin γ (IntC280) and EspB can reduce E. coli O157:H7 fecal shedding after experimental challenge. Shiga toxin (Stx) exerts local immunosuppressive effects in the bovine intestine and Stx2B fused to Brucella lumazine synthase (BLS-Stx2B) induces Stx2-neutralizing antibodies. To determine if an immune response against Stx could improve a vaccine’s effect on fecal shedding, groups of calves were immunized with EspB + IntC280, with EspB + IntC280 + BLS-Stx2B, or kept as controls. At 24 days post vaccination calves were challenged with E. coli O157:H7. Shedding of E. coli O157:H7 was assessed in recto-anal mucosal swabs by direct plating and enrichment followed by immunomagnetic separation and multiplex PCR. Calves were euthanized 15 days after the challenge and intestinal segments were obtained to assess mucosal antibodies. Vaccination induced a significant increase of IntC280 and EspB specific antibodies in serum and intestinal mucosa in both vaccinated groups. Antibodies against Stx2B were detected in serum and intestinal mucosa of animals vaccinated with 3 antigens. Sera and intestinal homogenates were able to neutralize Stx2 verocytotoxicity compared to the control and the 2-antigens vaccinated group. Both vaccines reduced E. coli O157:H7 shedding compared to the control group. The addition of Stx2B to the vaccine formulation did not result in a superior level of protection compared to the one conferred by IntC280 and EspB alone. It remains to be determined if the inclusion of Stx2B in the vaccine alters E. coli O157:H7 shedding patterns in the long term and after recurrent low dose exposure as occurring in cattle herds.